Writing Measurable Goals in Individual Education Plan (Annual of the Faculty of Philosophy in Skopje, 2017)
Since every child is unique, there is no pattern or standard format for writing measurable goals in individual education plan (IEP). Even two or more children with similar difficulties or even in the same condition (for example, autism or ADHD), will learn, develop and progress differently, and therefore, they cannot share a common IEP.It is very important for the individual plan to be in compliance with the curriculums and organization in the school, as well as to be clearly written and easily applicable. There shouldn’t be many goals, and set goals should express the expected positive achievements, not the things that the student is not able to achieve. Also, it is very important to put a focus on short-term and specific goals, and not to globalize with setting common goals.In this study we are going to present IEP for a student in the IV grade, put stress on assessment of current level of functional performance, discover their strengths and weaknesses, pay attention to writing measurable goals and indicate the procedures for measuring development regarding the annual goals.
Keywords: INDIVIDUAL EDUCATION PLAN; GOALS; STUDENT; TEACHER